PSYCHOLOGICAL HEALING THROUGH PROPHETIC SUPPLICATIONS: A CASE STUDY OF KITAB AL-DA‘AWAT OF JAMI AL-TIRMIDHI - Maryam Fatima (Journal of Religion and Society, 2025)
Psychological healing through prophetic supplications (du’a, plural ad’iah) is a significant component of Islamic tradition, offering a unique approach to mental health that integrates faith with healing practices. This paper explores the impact of prophetic supplications on psychological well-being, particularly focusing on the Kitab al-Da‘awat (Book of Supplications) from Jami al-Tirmidhi, a canonical work of Hadith literature. In Islamic tradition, these supplications are believed to have the potential to mitigate psychological ailments, such as anxiety, depression, addiction, and phobias, by fostering emotional and spiritual well-being. Healing through faith is common across various religious traditions, with devotional practices providing emotional support and spiritual healing to individuals. The study emphasizes the relevance of prophetic injunctions in addressing psychological ailments, particularly within the context of contemporary mental health challenges. It highlights how these spiritual practices, while deeply rooted in religious tradition, align with modern psychological principles and can offer beneficial tools for faith-based psychological healing in the Muslim community. As modern life becomes increasingly stressful due to socio-economic pressures and a disconnect from religious practices, many individuals seek solace in faith-based practices. The challenges of contemporary psychological health, including addiction, depression, and personality disorders, call for a closer examination of how religious practices, particularly prophetic supplications, can contribute to psychological healing. This paper aims to bridge the gap between religious healing practices and modern psychological theories, offering insights into the potential of faith-based interventions in managing mental health issues. Keywords: Prophetic Supplications, Psychological Healing, Islamic Tradition, Mental Health, Jami Al-Tirmidhi, Kitab Al-Da‘Awat, Faith-Based Healing, Contemporary Psychological Challenges, Spiritual Well-Being, Islamic Faith